Statistical indicators system characterizing state and course of modernization process as a factor of housing and public utility services system in regional development - R. Kh. Mutolapov (Вестник университета)
The article presents a study on the designed and proposed statistical indicators assessment that characterize the current state of the housing and public utility services system as a modernization factor in the constituent entities of the Russian Federation. The indicators affecting the process of innovative development as a factor of the system’s regional development have been evaluated. The analysis of scientific literature of domestic and foreign researchers studying the problem of the development in the context of the negative impact of pandemic and sanctions on the country’s economy has been presented. The main economic and designed indicators of the development have been evaluated. The results of the study conclude that the transformation of regional management on the development of housing and public utility services system should be further researched. The strategies for organizing such activities have been proposed.